Effect of Kshara Karma with Apamarga Pratisaraniya Kshara in Cervical Erosion - A Case Report (AYUSHDHARA, 2022)
Cervical erosion is the commonest causes of vaginal discharge in females, where ectocervix is covered by columnar epithelium, that means natural squamous epithelium is later replaced by columnar epithelium and appears like a Karnikakara granthi or Vrana depending upon the chronicity. The condition of cervical erosion is commonly treated in contemporary system of medicine with invasive therapies such as electric cauterization, cryosurgery etc. Kshara karma is a minimal invasive procedure that helps to destroy the ectopic columnar epithelium. So in the present study, a 40 year old woman diagnosed with cervical erosion (Karnini yonivyapad) was treated with Kshara karma using Apamarga Pratisarainiya kshara for 3 sittings each on alternate days for two cycles, starting from fifth day of the menstruation. After treatment significant reduction in the extent of cervical erosion was observed and the patient got relief in associated complaints. From this case study, it can be concluded that Kshara karma with Apamarga pratisaraniya kshara may be used as a safe and economical option for treating the cervical erosion.